Economic Analysis of the Determinants of Citrus Exports in South Africa Post the Era of Trade Liberalisation - Mushoni Bulagi; Tshepo Maxwell Lebepe; Jan Johannes Hlongwane (Wieś i Rolnictwo)
The purpose of the study was to analyse the determinants of South African citrus exports post era of trade liberalisations using secondary data from 1996 to 2018. The Johansen Cointegration model was used to test the long-run relationship between the citrus export and the determinants in the post era of trade liberalisation and Ordinary Least Squares regression was used to determine the relationship between citrus export in South Africa and the selected determinants post the era of trade liberalisation. The results of the Johansen Cointegration model show the existence of a long-run equilibrium relationship between citrus exports and the determinants of South African citrus exports. The Ordinary Least Squares regression results provided evidence that citrus production and citrus world market prices are the major influencers of citrus export in South Africa. The Department of Agriculture and the Citrus Associations should make initiatives to ensure an increase in citrus production by promoting development programmes for the citrus producers.